Kepemimpinan Visioner Kepala Sekolah dalam Meningkatkan Pendidikan Pariwisata - Syam, Aldo Redho; Nurjan, Syarifan; Kurnianto, Rido; Sumaryanti, Lilis; Handayani, Safitri Windi (Tahta Media Group, 2022)
This study aims to understand and analyze the visionary leadership of school principals in improving tourism education. Using this type of qualitative research with a phenomenological approach, the research target is at SMK Negeri 2 Ponorogo. Data collection techniques included in-depth interviews, participant observation, and documentation study. Data analysis techniques include data collection, condensation, data display, and drawing and verifying conclusions. The results showed that the principal's visionary leadership in improving tourism education at SMK Negeri 2 Ponorogo has been running effectively and efficiently by showing three dimensions: commitment, consistency, and competence. The principal's visionary leadership has also shown himself to be an “agent of change”, which consists of conceptual skills, technical skills, and human relations. The efforts of the principal of SMK Negeri 2 Ponorogo in improving tourism education are: (1) the ability of the principal to manifest his behaviour and attitude to his members; (2) the principal's ability to communicate verbally and non-verbally, supported by thinking out of the box; (3) the ability of the principal in identifying and solving problems with new techniques and methods and not being too cooperative; (4) the ability of the principal to leave doubts, be ready to take risks for innovation, and be open to doing different things; (5) the principal's ability to use the power of imagination, appreciation, intuition in making decisions.